Exploring motherhood dilemmas and coping strategies among mothers of children with autism: a qualitative study in mainland China - Zhou, Jun; Ning, Yuanhong (Frontiers in Psychiatry, 2025)
BackgroundUnder the traditional division of gender roles in China, mothers often shoulder more responsibilities for caring for children with autism. This article is the first attempt to explore the motherhood practices of mothers of autistic children.MethodThrough in-depth interviews with eight mothers, revealing three major themes: (1) the mothering dilemmas encountered by mothers of children with autism, (2) why mothers of autistic children choose to stay the course, and (3) the maternal adjustment practices of mothers of children with autism.ResultsThis study uncovers the challenges encountered during the nascent phases of these mothers’ parenting journeys. However, these mothers showed remarkable resilience and adaptability to these challenges. They also developed various motherhood adjustment strategies to cope with these dilemmas.ConclusionsThe findings emphasize the maternal resilience demonstrated by Chinese mothers of children with autism in the parenting process and the sources of this resilience. They provide new perspectives for understanding this group’s parenting practices, informing related policy development, and supporting service provision.